Cryosurgical posterior nasal tissue ablation for the treatment of rhinitis. Issue 10 (11th August 2017) - Hwang, Peter H.; Lin, Bryant; Weiss, Raymond; Atkins, James; Johnson, Jacob
Abstract : Background: Endoscopic posterior nasal nerve (PNN) resection has been described as an efficacious surgical treatment of allergic and nonallergic rhinitis, but the requirement for surgery under general anesthesia has limited its acceptance. We report the first series of patients treated for chronic rhinitis using a novel device designed for office‐based cryosurgical ablation of the PNN. Methods: Twenty‐seven patients with chronic rhinorrhea and/or nasal congestion for >3 months were recruited (allergic or nonallergic rhinitis), with minimum rhinorrhea and/or congestion subscores of 2 as part of the Total Nasal Symptom Score [TNSS]). Under local anesthesia, the cryotherapy device was applied endoscopically to the posterior middle meatus and was used to freeze the PNN region bilaterally. Patients were followed up after 7, 30, 90, 180, and 365 days to assess TNSS. Results: The procedure was successfully completed in 100% of patients, with no complications; 74% reported no or mild discomfort by the first postprocedure day. TNSS was reduced significantly at 30 days (mean ± standard deviation: 6.2 ± 0.5 at baseline, 2.6 ± 0.3 at 30 days, n = 27, p < 0.001), with continued reduction at 90 (2.7 ± 0.4, n = 24, p < 0.001), 180 (2.3 ± 0.5, n = 21, p < 0.001), and 365 days (1.9 ± 0.3, n = 15, p < 0.001). Both rhinorrhea and congestion subscores decreased significantly at 30, 90, 180, and 365 days compared to baseline ( p < 0.001). Allergic and nonallergic subcohorts both appeared to benefit from treatment. Conclusion: Office‐based cryotherapy of the PNN region is safe and well tolerated. Symptom scores were significantly decreased by 7 days postprocedure and remained lower at 30, 90, 180, and 365 days.